An anthropometric study to evaluate the correlation of vertical dimension at rest and length of thumb: A multi-national, multi-centre pilot study - M C Suresh Sajjan; Prashanti Eachempati; Rupinder Singh Dhall; Deepthi Fulari; Kamal Shigli; Htoo Htoo Kyaw Soe (Wolters Kluwer Medknow Publications, 2020)
Aim: A variety of anthropometric techniques have been proposed to determine the correct vertical dimension of occlusion. However, none have reported correlating thumb length (TL) with vertical dimension at rest (VDR). This study aimed to correlate the VDR to measurements of the thumb in a multi-national, multi-centric trial in participants with and without orthodontic treatment and establish a regression equation for each region. Settings and Design: A cross-sectional multi-national, multi-centric correlation trial. Materials and Methods: A cross-sectional study was conducted in India and Malaysia with a total of 688 participants. Measurements of thumb and VDR were obtained using a modified Willi's gauge using a standard operating procedure. Statistical Analysis Used: Pearson's correlation coefficient was calculated to determine the correlation between TL and VDR. A multiple linear regression was done to correlate VDR from gender, orthodontic treatment, and length of thumb. Results: Correlation coefficient between TL and VDR in patients with orthodontic treatment was 0.829 and 0.774 in patients without orthodontic treatment. The correlation between TL and VDR in patients with orthodontic treatment in North India was 0.484, P = 0.010 and Malaysia was 0.946, P < 0.001. There were significant correlations between TL and VDR in patients without orthodontic treatment in all regions (P < 0.001). Regression equations were obtained for different ethnic groups for calculating the VDR. Conclusion: There was an overall positive correlation between TL and VDR in patients with and without orthodontic treatment. The regression equations presented in this article could help clinicians in their clinical practice and researchers to conduct future trials.